2012
DOI: 10.1097/mcg.0b013e3182372541
|View full text |Cite
|
Sign up to set email alerts
|

Serological Tests in Gluten Sensitivity (Nonceliac Gluten Intolerance)

Abstract: The serological pattern of GS is characterized by IgG AGA positivity in more than half of cases associated to IgA AGA in a few patients, but without EmA, tTGA, and DGP-AGA, which are the specific markers of celiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
198
5
25

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(238 citation statements)
references
References 22 publications
10
198
5
25
Order By: Relevance
“…All the patients had normal anti-gliadin levels. So far, this is the only candidate marker of such a condition [30]. In this context, the presence of intestinal autoantibodies against TG2 should be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients had normal anti-gliadin levels. So far, this is the only candidate marker of such a condition [30]. In this context, the presence of intestinal autoantibodies against TG2 should be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Further supportive evidence has come from an Italian group who have reported a high prevalence of IgG gliadin in glutensensitive patients ( n = 44 / 78 or 56.4 % ) ( 45 ). Finally, a recent report of a gluten challenge in a double-blind randomized placebo-controlled study of IBS patients self-controlled on a GFD ( n = 34) suggested that " non-celiac gluten intolerance " may exist ( 46 ).…”
Section: What Evidence Is There To Support the Concept Of Non-celiac Gs?mentioning
confidence: 93%
“…The role of anti-gliadin antibodies (AGA): AGA IgA and IgG have been found in 50% of patients with NCGS [15]; in another study [17] AGA IgG were found at high titre in 56.4% of NCGS patients, while AGA IgA were found in 7.7% of cases.…”
Section: Atis -Amylase Trypsin Inhibitors Non-gluten Derived Proteinsmentioning
confidence: 99%